The Potential of Native Tree Species for Post-Nickel Mining Land Restoration - Suhati, Fadly; Ngakan, Putu Oka; Maulany, Risma Illa; Nasri, Nasri; Hamzah, Andi Siady; Putra, Putu Supadma (Foresty Faculty of Hasanuddin University, 2025)
Due to the absence of topsoil, low pH, and contamination by various heavy metals, revegetation of post-nickel mining land, which is generally carried out by planting economically valuable species, is usually unsuccessful. This study aims to identify tree species suitable for revegetation on post-nickel mining land in Kolaka Regency, Indonesia. Nine plots measuring 20 m x 20 m were distributed in the revegetated post-nickel mining land at three different age categories (1, 5, and 10 years) to observe the growth of revegetation trees, which are introduced species and native tree species that naturally invade the revegetation area. In total, there were 24 tree species found in the revegetated post-nickel mining land consisting of 9 introduced revegetation species and the other 15 tree species were native tree species that invaded the revegetated area. The older the age of the revegetation, the more native plant species are found. In line with the increasing age of revegetation, the density of revegetation plants decreases while the density of native plants increases. The population structure of revegetation trees does not indicate that the species can regenerate, while the inverted shape of the population structure of native plants indicates excellent regeneration potential. Thus, the results of this study recommend making native species, including Buchanania arborescens, Alstonia macrophylla, Ficus sp. Syzygium sp. Colona scabra, Litsea sp., and Metrosideros cf. petiolata as revegetation plants in former nickel mining areas.